Studies on Slip Casting Control (V): Relationship between Properties of Cast Whiteware Bodies and the Fundamental Parameters of Slips - WATANABE, Nobuhiko (Journal of the Ceramic Association, Japan, 1972)
Investigating some properties of casting layers in molds, the following results were obtained. 1) Inhomogeneous moisture distribution in cast pieces on draining resulted from the moisture gradient in cast layers which was proportional to the product of the fundamental parameters, [F3⋅Sa⋅ds], and from the thickness of remaining slip layers which could be expressed as a function of yield value, viscosity and drain angle. 2) Average solid volume fraction of cast pieces on draining, [Fc], was calculated from the equation Fc=(Fc′l+F1Δl)/(l+Δl) where Fc′, F1, l and Δl were solid volume fraction of cast layers, of remaining slip layers, thickness of cast layers, and of remaining slip layers, respectively. Fc′ was expressed by the equation Fc′={0.55/(1+Sa⋅ds)-0.44}⋅F3+0.01F1. 3) In the case of solid casting, the average solid volume on bulding up of the cast layers could approximately be estimated by the above equation giving Fc′ value. 4) On draining or building-up of the cast layers the initial moisture content in cast layers rapidly decreased until mold separation stage having the solid volume fraction, FD. It was suggested that workability of demolded cast pieces would depend upon the value of [(FD-FC)/FD]. 5) Dry linear shrinkage, Sh, could be expressed by the equation Sh=A(1-FC/F3) where A was a constant depending upon the anisotropy in shrinkage.